The Application of Meditation/Mindfulness Therapy for Stress and Insomnia in the Elderly: A Literature Review - Safrudin, Bachtiar; Widyastuti, Dwi; Anata, Agil; Almadaniyah, Hanun; Azzahrah, Sekar Putri; Amanda, Devi Clarisa; Nurjanah, Nurjanah; Khalizah, Nur; Putri, Anisa Duwi; Safitri, Dwi Amelia; Sadien, Rayshifa; Anggreini, Niken (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Older adults often experience psychological and physiological changes that lead to stress and sleep disorders such as insomnia. Mindfulness and meditation therapy have been widely applied as non-pharmacological interventions to improve sleep quality and reduce anxiety among elderly populations. This literature review aims to analyze and synthesize evidence from Indonesian studies regarding the effectiveness of meditation and mindfulness therapy in reducing stress and insomnia in older adults. Method: A literature review was conducted using Google Scholar, Garuda, and Neliti databases for Indonesian studies published from 2019–2025. Eighteen eligible articles were analyzed, including three local studies by Bachtiar Safrudin focusing on yoga, physical activity, and elderly exercise as relaxation interventions. Result: Most studies demonstrated that meditation and mindfulness significantly reduce stress and improve sleep quality in the elderly. Local findings also supported these effects through yoga and relaxation exercises. Conclusion: Meditation and mindfulness are effective, simple, and safe interventions that can be integrated into community-based nursing programs to enhance elderly mental health.